2017
DOI: 10.1523/jneurosci.3680-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Enhanced Phrenic Long-Term Facilitation in SOD1G93A Rats

Abstract: Amyotrophic lateral sclerosis (ALS) is a degenerative motor neuron disease, causing muscle paralysis and death from respiratory failure. Effective means to preserve/restore ventilation are necessary to increase the quality and duration of life in ALS patients. At disease end-stage in a rat ALS model (SOD1 G93A), acute intermittent hypoxia (AIH) restores phrenic nerve activity to normal levels via enhanced phrenic long-term facilitation (pLTF). Mechanisms enhancing pLTF in end-stage SOD1 G93A rats are not known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Phrenic motor neuron death is relatively stable once it is induced by CTB-SAP ( i.e. comparison of 7 and 28 day CTB-SAP treated rats indicate no statistical difference in phrenic motor neuron death; Nichols et al, 2015b; Figure 1), and is similar to phrenic motor neuron death that has been observed in end-stage SOD1 G93A rats (Nichols et al, 2013a; 2013b; 2015a; 2017). Thus, differential phrenic motor neuron death alone (Figure 1) does not account for the differential pLTF that is exhibited following 7 and 28 days of CTB-SAP (Figures 3–5).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Phrenic motor neuron death is relatively stable once it is induced by CTB-SAP ( i.e. comparison of 7 and 28 day CTB-SAP treated rats indicate no statistical difference in phrenic motor neuron death; Nichols et al, 2015b; Figure 1), and is similar to phrenic motor neuron death that has been observed in end-stage SOD1 G93A rats (Nichols et al, 2013a; 2013b; 2015a; 2017). Thus, differential phrenic motor neuron death alone (Figure 1) does not account for the differential pLTF that is exhibited following 7 and 28 days of CTB-SAP (Figures 3–5).…”
Section: Discussionmentioning
confidence: 65%
“…This latter pathway either constrains pLTF during moderate AIH, or elicits enhanced A 2A receptor dependent pLTF in response to severe AIH (Hoffman et al, 2010; Nichols et al, 2012). Since 7 day CTB-SAP treated rats exhibit enhanced pLTF (Figures 2 and 4A), it is possible that the underlying mechanism: 1) is similar to that utilized in SOD1 G93A rats (BDNF synthesis and MEK/ERK dependent pLTF; Nichols et al, 2017); 2) switches to the A 2A receptor dependent pathway to express enhanced pLTF; or 3) requires both the G q and G s pathways as has been observed following chronic intermittent hypoxia (Ling et al, 2001; McGuire et al, 2004). In contrast, pLTF is still present but enhancement is lost in 28 day CTB-SAP treated rats (Figures 4 and 5A), and it remains unknown if pLTF simply returns to normal and requires the G q and/or the G s pathway or if pLTF is being constrained by peripheral and/or local influences such as inflammation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, recovering the BDNF signaling is a good option for ALS therapy, due to its strong pro-survival effects through TrkB and p75 NTR in developing and injured MN [122][123][124]. However, because intrathecally administered exogenous BDNF does not improve motor function and survival in ALS patients [108] or autonomic nervous system function [109,125], it is essential to target the altered alternative splicing of the TrkB, as it is strongly related to the maintenance of NMJs done by the bidirectional synaptic and neurotrophic controls, as has already been pointed out.…”
Section: Bdnf/trkb Signaling Is Impaired In Als Nmjmentioning
confidence: 99%
“…Although central serotonergic neurons degenerate in rodents models (87) and patients with ALS (88), mAIH-induced pLTF is enhanced in late-stage SOD1 G93A rats, and the underlying mechanisms remain 5-HT-2 receptor and BDNF-dependent, suggesting that it arises from amplification of the same fundamental mechanism (89). Enhanced pLTF is also observed following intrapleural CTB-Saporin-induced phrenic motor neuron death (90), suggesting that motor neuron death per se is sufficient to elicit certain forms of spinal respiratory motor plasticity.…”
Section: Spinal Synaptic Plasticity At the Phrenic Motor Nucleusmentioning
confidence: 99%